2009
DOI: 10.1073/pnas.0910280107
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary branched chain amino acids ameliorate injury-induced cognitive impairment

Abstract: Neurological dysfunction caused by traumatic brain injury results in profound changes in net synaptic efficacy, leading to impaired cognition. Because excitability is directly controlled by the balance of excitatory and inhibitory activity, underlying mechanisms causing these changes were investigated using lateral fluid percussion brain injury in mice. Although injury-induced shifts in net synaptic efficacy were not accompanied by changes in hippocampal glutamate and GABA levels, significant reductions were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 27 publications
10
139
0
Order By: Relevance
“…Further studies employed a mix of molecular biology techniques and electrophysiology to investigate the mechanism behind the observed imbalance of excitatory/inhibitory synaptic transmission (11). Importantly, these studies employed behavior not only to demonstrate a cognitive impairment post-TBI, but also to validate the effectiveness of a dietary treatment strategy derived from the results gained from using our combinatorial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies employed a mix of molecular biology techniques and electrophysiology to investigate the mechanism behind the observed imbalance of excitatory/inhibitory synaptic transmission (11). Importantly, these studies employed behavior not only to demonstrate a cognitive impairment post-TBI, but also to validate the effectiveness of a dietary treatment strategy derived from the results gained from using our combinatorial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Branched chain amino acids (BCAAs) are key amino acids involved in de novo glutamate synthesis [142]. We have found that dietary BCAA therapy restores limbic E/I balance and ameliorates hippocampal-dependent contextual fear memory impairment in a mild/moderate FPI mouse model [143]. Furthermore, we have demonstrated that BCAA therapy mitigates injury-induced inability to maintain wakefulness [144••].…”
Section: Potential Therapeutic Strategies To Improve Memory Dysfunctimentioning
confidence: 99%
“…Local to global neurological dysfunction associated with TBI is not only caused by the primary immediate insult, but is also caused by the delayed secondary cascade of biochemical and metabolic pathological events. These include impaired aerobic metabolism, altered calcium homeostasis, disrupted amino acid metabolism, and activated inflammatory responses (Alves et al, 2005;Bartnik et al, 2007;Cole et al, 2010;Deshpande et al, 2008;Faria et al, 2007;He et al, Traumatic brain injury is not a single entity. Rather it is a disorder caused by multiple mechanisms, including low-and high-velocity penetrating injury, blunt trauma, diffuse axonal injury, and blast.…”
Section: Introductionmentioning
confidence: 99%